2013
DOI: 10.4103/0974-7753.125608
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and dermatoscopic patterns of alopecia areata: A tertiary care centre experience

Abstract: Background:Dermatoscopy is a new noninvasive tool for the diagnosis of various skin and hair disorders. Dermatoscopy of alopecia areata (AA) shows various specific features, which may aid in confirming the diagnosis.Aims:The aim of this study was to determine the various clinical patterns and the dermatoscopic features of AA.Materials and Methods:A total of 75 patients of AA were evaluated with a dermatoscope (magnification ×25 and ×60).Results:The mean age of onset of AA was 23.58 years. Males were more commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 10 publications
2
23
0
Order By: Relevance
“…[91011] However, some studies reported lesser incidence. [71213] This variation in results can be attributed to the difference in skin types (yellowish color of skin in Asians may make it difficult to perceive the YDs on dermoscopy), different shampooing habits, and difference in the type of dermoscope used. [714] In view of their higher frequency in AA as reported by various studies including ours, YD can be regarded as a sensitive marker for the diagnosis of AA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[91011] However, some studies reported lesser incidence. [71213] This variation in results can be attributed to the difference in skin types (yellowish color of skin in Asians may make it difficult to perceive the YDs on dermoscopy), different shampooing habits, and difference in the type of dermoscope used. [714] In view of their higher frequency in AA as reported by various studies including ours, YD can be regarded as a sensitive marker for the diagnosis of AA.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported lesser incidence. [71112] These variations in results may be due to difference in activity, severity, and duration of the disease in various studies. [15]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients were diagnosed to have active alopecia areata by history of active hair loss within the past 6 months [ 9 ], positive pull test [ 10 ], exclamation mark hair seen clinically at the periphery of the lesions [ 11 ] and trichoscopic examinations showing black dots, broken hair and exclamation marks [ 12 ]. The extent of the scalp involvement was further evaluated using the Severity Alopecia Tool (SALT) [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…They represent increased follicular blood supply and their presence signify a better prognosis with respect to hair regrowth. 8,9 Androgenetic alopecia (AGA) is characterized by hair diameter diversity due to miniaturization of the hair follicles. Variability in hair shafts diameter of more than 20% is diagnostic of this condition.…”
Section: Introductionmentioning
confidence: 99%